2017
DOI: 10.2337/db16-1074
|View full text |Cite
|
Sign up to set email alerts
|

SOX4 Allows Facultative β-Cell Proliferation Through Repression of Cdkn1a

Abstract: The high-mobility group box transcription factor SOX4 is the most highly expressed SOX family protein in pancreatic islets, and mutations in are associated with an increased risk of developing type 2 diabetes. We used an inducible β-cell knockout mouse model to test the hypothesis that is essential for the maintenance of β-cell number during the development of type 2 diabetes. Knockout of at 6 weeks of age resulted in time-dependent worsening of glucose tolerance, impairment of insulin secretion, and diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
(33 reference statements)
2
24
0
Order By: Relevance
“…4; Additional file 9: Figure S8) as candidate functional genes, including SOX4 ([PCS = 0.62] at the locus usually named for CDKAL1 ) and ATXN7 ([PCS = 0.57] at the locus named for ADAMTS9 ). In the former case, our prioritisation of SOX4 has been validated by subsequent experimental studies which have demonstrated a direct relationship between perturbation of SOX4 and insulin secretion and beta-cell proliferation ([50, 51]).…”
Section: Resultsmentioning
confidence: 67%
“…4; Additional file 9: Figure S8) as candidate functional genes, including SOX4 ([PCS = 0.62] at the locus usually named for CDKAL1 ) and ATXN7 ([PCS = 0.57] at the locus named for ADAMTS9 ). In the former case, our prioritisation of SOX4 has been validated by subsequent experimental studies which have demonstrated a direct relationship between perturbation of SOX4 and insulin secretion and beta-cell proliferation ([50, 51]).…”
Section: Resultsmentioning
confidence: 67%
“…Moreover, recent studies found that Sox4 has a role in insulin secretion in adult b-cells and that mutations in the Sox4 gene are associated with an increased risk of developing type 2 diabetes (22)(23)(24). Mechanistic studies further showed that Sox4 allows b-cell proliferation and replication through direct repression of p21 CIP1 (25). In addition, expression of Sox4 was also shown to participate in skeletal muscle differentiation (26).…”
mentioning
confidence: 99%
“…SOX4 is an important member of the SOX transcription factor family, and interference with its expression inhibits tumor cell proliferation and promotes apoptosis. 23 SOX4 plays a critical role in the development of colorectal cancer. The high expression of SOX4 can inhibit the proliferation and invasion of colorectal cancer cells.…”
Section: Introductionmentioning
confidence: 99%